Problématiser les enjeux professionnels de la laïcité à partir d'expériences difficiles vécues par des enseignants dans des classes de quartiers populaires - Bruno Fondeville
This article is related to the academic secularism challenges in the educational field. Social plan and policy level are analyzed from the stresses issue of the french society. A focus is given on teaching practices, in popular neighbourhood, faced with disruptive situations. Twenty teachers were interviewed about the way they handled these situations. They show the impossibility to solve these situations by only considering the french legal framework. This investigation reports trade-off practices, source of individual initiative who question the definition, the position and the practice of secularism inside of republican school.